2019
DOI: 10.1002/pon.5245
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and its correlates in people living with lung cancer: A cross‐sectional study from China

Abstract: Objectives: This study aimed to examine the level of stigma and identify the correlates of stigma among lung cancer patients in China.Methods: In total, 283 lung cancer patients were recruited from a tertiary cancer center in China by the convenience sampling method and completed a demographic, disease-related information and situational characteristics questionnaire and selfreported measures assessing stigma, state self-esteem, and coping self-efficacy.Results: The mean stigma score was moderate (2.38 ± 0.45)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
(113 reference statements)
3
30
0
Order By: Relevance
“…Higher stigma experiencing was found in male patients than female, particularly in youth aged 18 ~ 44. That results were consistent with previous qualitative [39], quantitative studies [25,40] or systematic review [13]. Male individuals, under the age of 18 ~ 44 was actively involved in their life.…”
Section: Demographic and Clinical Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…Higher stigma experiencing was found in male patients than female, particularly in youth aged 18 ~ 44. That results were consistent with previous qualitative [39], quantitative studies [25,40] or systematic review [13]. Male individuals, under the age of 18 ~ 44 was actively involved in their life.…”
Section: Demographic and Clinical Characteristicssupporting
confidence: 92%
“…Among them, the greatest contributor was acceptance-resignation, followed by confrontation (Table 3). [11,24,25] that using SIS to assess stigma of HIV or cancer. As compared to latest studies of them, AL patients scored higher than lung cancer [13] and prostate cancer [14], but lower than HIV [11], colorectal cancer with stoma [12] and breast cancer [14].…”
Section: In Factors Of Stigma In Patients Newly Diagnosed With Almentioning
confidence: 99%
See 1 more Smart Citation
“…People with lung cancer report high levels of psychological distress 15 . In particular, lung cancer stigma has been found to be associated with a number of outcomes related to psychological distress such as depression, poor health‐related quality of life, low coping self‐efficacy and greater symptom burden 11,16–19 . Findings from longitudinal studies of lung cancer populations suggest psychological distress can be enduring or heightened over the cancer trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in patients under negative health conditions showed they feel stigmatized and reported feelings of exclusion, rejection or devaluation (Weiss et al, 2006). Stigma-induced discrimination in turn, has been associated with different negative outcomes such as more psychological distress (Berjot and Gillet, 2011), more depressive symptoms (Roberts et al, 2020) less self-esteem (Liu et al, 2020) and the reduction of perceived quality of life (Chambers et al, 2012(Chambers et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%